Dīwān-i ashʿār-i Fahmī Astarābādī - Astarābādī, Fahmī (Miras Maktoob, ISBN: 9789004365452., 2019)
This is a collection of poems, mostly ghazals, by the otherwise little-known 10th/16th century poet Fahmī Astarābādī. All that the available sources tell us about him is that he was talented and intelligent, that (as a young man?) he went to India, that he earned a living in business, and that he died in Delhi. Thanks to the research of the editor of his divan, we now know somewhat more. First, that Fahmī spent a certain time in the entourage of Rustam Rūzafzūn (d. 917/1511), ruler of Mazandaran and that he also wrote poetry in praise of some of the other members of that family; that he lived in Yazd for two years and lost his fortune there, returning broke to Mazandaran; that he travelled to Najaf, Mecca and Mashhad; and that he was in India when Sultan Bābur died in 937/1530. Alive in 948/1541, is not known when or where he passed away.